Outcome of Immediate Interventions in Acute Dysfunctional Hemodialysis Fistulas - Schaefer, P. J.; Jahnke, T.; Müller-Hülsbeck, S.; Wulff, A. M.; Sattler, B.; Schmidt, M.; Siggelkow, M.; Schaefer, F. K. W. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To analyze the efficacy of interventions in acute dysfunctional hemodialysis fistulas, if intervention is performed immediately as recommended by European Best Practice Guidelines for Hemodialysis. Materials and Methods: Over 3 years, all (n = 280) patients with an acute dysfunctional hemodialysis fistula were immediately referred to angiography, irrespective of the time of day. Angiography and, if possible, interventional revision (n = 241) were performed. Three groups of interest were established: interventionalist’s experience (high/low), time of day (routine hours: 7 am–4 pm/emergency hours: 4 pm–7 am), lesion type (stenosis/fibrosclerotic occlusion/thrombotic occlusion/combined stenosis+thrombotic occlusion). For statistical analysis corresponding success rates, chi-square tests (p < 0.025) and logistic regression analysis (p < 0.05) were calculated. Results: The total success rate was 62 % (149/241). The success rates were: interventionalist experience high/low 71 % (79/111)/54 % (70/130), p = 0.022; time of day routine/emergency hours 68 % (93/136)/53 % (56/105), p = 0.017; lesion type stenosis/fibrosclerotic occlusion/thrombotic occlusion/combined stenosis+occlusion 82 % (94/104)/39 % (13/33)/18 % (6/33)/59 % (36/61), p < 0.001. Relevant variables due to logistic regression analysis were high experience and the lesion types stenosis and combined stenosis+occlusion with odds ratios 2.300 (p = 0.012), 12.053 (p < 0.001), 3.189 (p = 0.003). Conclusion: Unrestricted implementation of immediate interventions in acute dysfunctional hemodialysis fistulas requires permanent availability of experienced interventionalists. The lesion types fibrosclerotic occlusion and thrombotic occlusion offer poor success rates for interventional revision.
Keywords: vascular; interventional procedures; efficacy studies; hemodialysis fistula